Exploring factors influencing electric vehicle usage intention: An empirical study in malaysia - Sang Y.-N.; Bekhet H.A. (Universiti Malaysia Sarawak, 2023)
The rationale of this study is to investigate the factors influencing electric vehicle usage intention in Malaysia. Empirical study using survey questionnaires are distributed to a judgment sampling of 500 drivers in Selangor and Federal Territories (Kuala Lumpur and Putrajaya). A research model based on the Theory of Planned Behavior was proposed as the underlying framework to realize the objective of the study. Linear regression-stepwise technique was used to test the research hypotheses. The results finding indicated that the electric vehicle usage intention in Malaysia is very much influenced by Environmental Concern, Consumer Knowledge, Psychological Benefits and Demographics. Hence, this paper provides valuable information for automotive players planning to market electric vehicles in Malaysia. It offers insights for formulation of marketing strategies that will address the real wants and needs of their future clients based on the identified factors in this study. Meanwhile, policy makers should formulate appropriate intervention and policies to encourage the growth of electric vehicles usage in Malaysia as a strategy to increase energy efficiency, reduce carbon emissions and minimize the reliance on fossil fuel in the automotive sector. Future study is suggested to be done to explore more factors that might influence public acceptance and to improve characterization of respondents by including more cities in Malaysia. 2015, Universiti Malaysia Sarawak, All Rights Reserved.